INTERACTIVE VIRTUALIZATION IN THE ENVIRONMENT OF FLASH-CC, JAVA SCRIPT OF ALGORITHMS THE PHENOMENON OF THERMOPHYSICS AND MOLECULAR PHYSICS, AS ACHIEVEMENT OF HIGHLY EFFECTIVE TRAINING - A.M. Tatenov; V.V. Savelyev; N.A. Sandibayeva; L.S. Baykadamova; D.Baitukayeva (Academic Scientific Journal of Computer Science, 2019)
The training program assumes not only studying of theoretical material, but also performance of laboratory works. They are necessary for development of skills of measurement of physical quantities, performance of physical experiences, ability to draw the correct conclusions from the observations. Modern computer technologies allow to add this traditional scheme of training. The training programs modeling physical processes and the phenomena which not always manage to be shown "in live" in the training conditions can provide to pupil’s substantial assistance. Processes of the phenomenon of molecular physics and thermophysics are visualized and online virtualized by means of the computer program environments Adobe Flash-CC, Java script. The made, laboratory work on a research of processes of the phenomenon of molecular physics and thermophysics is very effective at development of this course, and the technology of creation of the virtual and interactive laboratory described in this article is very relevant for creation of the similar virtual and interactive laboratories (VIL) in other objects. This virtual interactive laboratory development is introduced in educational process of the Eurasian technological university and is successfully applied in training